Answer:
x = 3 , y = 0
Step-by-step explanation:
Solve the following system:
{y = (2 x)/3 - 2 | (equation 1)
y = 3 - x | (equation 2)
Express the system in standard form:
{-(2 x)/3 + y = -2 | (equation 1)
x + y = 3 | (equation 2)
Swap equation 1 with equation 2:
{x + y = 3 | (equation 1)
-(2 x)/3 + y = -2 | (equation 2)
Add 2/3 × (equation 1) to equation 2:
{x + y = 3 | (equation 1)
0 x+(5 y)/3 = 0 | (equation 2)
Multiply equation 2 by 3/5:
{x + y = 3 | (equation 1)
0 x+y = 0 | (equation 2)
Subtract equation 2 from equation 1:
{x+0 y = 3 | (equation 1)
0 x+y = 0 | (equation 2)
Collect results:
Answer: {x = 3 , y = 0